2017
DOI: 10.1192/bjpo.bp.116.004317
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol and drug use in youth and adults with attention-deficit hyperactivity disorder

Abstract: BackgroundPrevious research suggests a relationship between attention-deficit hyperactivity disorder (ADHD) and smoking, alcohol and illicit drug use, however most studies have focused on adolescents or young adults, or clinically ascertained samples.AimsTo analyse population-based data on the relationship between ADHD and at-risk health behaviours in adolescents and adults.MethodData were derived from a Statistics Canada population-based health survey. The association between the diagnosis of ADHD and smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Our results show that ADHD was associated with SUD in adolescence and that girls with ADHD were at an increased risk for some types of SUD, including tobacco, alcohol, marijuana, and cannabis [43][44][45][46]52,55,59]. Indeed, the body of research suggesting that girls with ADHD may be at increased risk for SUD is growing [29,32,34,[61][62][63][64]. Two studies, by Biederman et al (2002) [65] and Biederman and Faraone (2004) [66], indicated that ADHD in girls was a greater risk factor for SUD than ADHD in boys, noting that girls with the disorder were at particular risk in early adolescence.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results show that ADHD was associated with SUD in adolescence and that girls with ADHD were at an increased risk for some types of SUD, including tobacco, alcohol, marijuana, and cannabis [43][44][45][46]52,55,59]. Indeed, the body of research suggesting that girls with ADHD may be at increased risk for SUD is growing [29,32,34,[61][62][63][64]. Two studies, by Biederman et al (2002) [65] and Biederman and Faraone (2004) [66], indicated that ADHD in girls was a greater risk factor for SUD than ADHD in boys, noting that girls with the disorder were at particular risk in early adolescence.…”
Section: Discussionmentioning
confidence: 63%
“…This means that the disorder itself is considered a risk factor for SUD [30,31]. Follow-up studies have highlighted a higher prevalence of substance use in the population of adolescents with ADHD relative to the general population [32][33][34]. Nonetheless, a review on sex differences in relation to the disorder has never been published.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that some drug abusers tend to use drugs or alcohol to mitigate their unpleasant emotional states (11). According to research reports, the relationship between the psychological state and drug abuse has been confirmed in most studies (12).…”
Section: Introductionmentioning
confidence: 99%
“…The association between ADHD and CAD/COPD is likely mediated by a variety of factors. First, heavy alcohol use has been associated with ADHD (Brinkman et al, 2015;Charach et al, 2011;Osland et al, 2017) and is considered a risk factor for CAD (Mostofsky et al, 2016;Roerecke et al, 2011;Roerecke and Rehm, 2010). Second, those with ADHD are more likely to be or have been a frequent smoker (Kollins et al, 2005;Milberger et al, 1997;Osland et al, 2017;Pomerleau et al, 1995), and smoking is in turn a risk factor for both CAD (Hackshaw et al, 2018) and COPD (Pauwels et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First, heavy alcohol use has been associated with ADHD (Brinkman et al, 2015;Charach et al, 2011;Osland et al, 2017) and is considered a risk factor for CAD (Mostofsky et al, 2016;Roerecke et al, 2011;Roerecke and Rehm, 2010). Second, those with ADHD are more likely to be or have been a frequent smoker (Kollins et al, 2005;Milberger et al, 1997;Osland et al, 2017;Pomerleau et al, 1995), and smoking is in turn a risk factor for both CAD (Hackshaw et al, 2018) and COPD (Pauwels et al, 2001). However, ADHD has also been linked to lower educational attainment (EA) (Polderman et al, 2010), which in turn has been associated with CAD (Kubota et al, 2017;Qureshi et al, 2003), COPD (Gjerdevik et al, 2015), and increased drinking frequency and smoking initiation (Latvala et al, 2014).…”
Section: Introductionmentioning
confidence: 99%